Dispositifs techniques de la micro-hydroélectricité et reconfiguration d’un territoire touristique de haute montagne (région de l’Everest, Népal) - Véronique André-Lamat; Isabelle Sacareau (Développement Durable et Territoires)
This article analyses the territorial reconfigurations related to the introduction of micro-hydropower in the hydrosocial cycle of the tourist region of Everest, where the use of wood is strictly regulated (Sagarmatha National Park). Numerous micro-power stations of varying power levels and unequal quality are the result of local initiatives supported by a variety of actors, operating at different scales. The analysis of the location of the infrastructure chain shows on the one hand that this technical device fits into a hydrosocial cycle now controlled by the tourist activity that has improved the living conditions of the population; on the other hand, the transition from water (source) to energy (resource), has revealed and generated socio-spatial inequalities.